Pengaruh Work Life Balance (WLB) terhadap Retensi Petugas Aviation Security (AVSEC) di Yogyakarta International Airport (YIA) - Galuh Eka Nofindra; Walid Jumlad (MES Bogor, 2025)
Aviation Security (AVSEC) officers often face challenges in balancing work demands with personal needs or what is also called Work Life Balance (WLB). The high rate of employee turnover in the aviation industry has become a significant challenge for companies, especially in the context of employee retention. The purpose of this study was to determine whether there is an effect of Work Life Balance (WLB) on the retention of Aviation Security (AVSEC) officers at Yogyakarta International Airport (YIA) and to determine the magnitude of the effect of Work Life Balance (WLB) on the retention of Aviation Security (AVSEC) officers at Yogyakarta International Airport (YIA). This study adopts a quantitative research design with a data collection technique using a Likert scale-based questionnaire. The study was conducted at the Aviation Security (AVSEC) unit of PT Angkasa Pura Indonesia Yogyakarta International Airport (YIA) from August 1 to September 30, 2024, where Aviation Security (AVSEC) officers at Yogyakarta International Airport (YIA) were the objects of this study. The research sample consisted of 71 officers, which were determined using the Slovin formula. Data analysis involved descriptive statistical tests, instrument tests (validity and reliability), and hypothesis tests using simple linear regression, T-tests, and coefficient of determination (R²) tests. The results of the study indicate that there is an influence of Work Life Balance (WLB) on the retention of Aviation Security (AVSEC) officers at Yogyakarta International Airport (YIA), as evidenced by the t-value being greater than the T-table value, which is 4,604 > 1,994. The R² value is known to be 0,235, meaning that Work Life Balance (WLB) has an effect on the retention of Aviation Security (AVSEC) officers at Yogyakarta International Airport (YIA) by 23,5%.